Kajian Etnosains pada Batik Lasem sebagai Nilai Ilmiah Terintegrasi Budaya Lokal - Okyranida, Indica Yona; Maghfiroh, Qisthi; Bhakti, Yoga Budi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2024)
This study explores the ethnoscience in Batik Lasem, a cultural heritage of Indonesia rich in scientific and aesthetic values. The research aims to identify and analyze the traditional knowledge embedded in the motifs and techniques of Batik Lasem, and how these values are integrated into the local community's life. The research methods include literature review, direct observation, and interviews with batik artisans and cultural experts. The findings reveal that Batik Lasem is not only an artistic expression but also reflects a deep understanding of local ecology, natural dyeing, and philosophy of life. The scientific values found in the batik-making process, such as the use of natural materials and eco-friendly dyeing techniques, demonstrate great potential for integration with modern science. The study concludes that Batik Lasem can serve as a medium for education and cultural preservation, as well as an inspiration for the development of science based on local culture